Maderas fósiles de Combretaceae de la Formación El Palmar (Pleistoceno), Entre Ríos, Argentina - Brea, Mariana (2001)
Petrified wood of a new species of Terminalioxvlon Schonfeld from the El Palmar Formation (Upper Pleistocene), Concordia, Entre Rios, Argentina, is described. The comparison with members of Combretaceae shows that Terminalioxulon concordiensis nov. sp. is different from other known fossil species and is similar to the extant genus Terminalia L. and close to T. triflora (Gris.) Lillo. Tcrminalioxulon concordiensis presents growth rings delimited by small vessels and narrow lines of terminal parenchyma. Vessels have diffuse porous, are mostly solitary, sometimes in radial multipleseriesof 2-3, rarely 4 elements, simple perforation plate. Ray system is homogenous. Rays are homocellular, frecuently uniseriate, rarely uniseriate with biseriate portion. Fibres are hexagonal, septate and abundant. Apotracheal axial parenchyma is diffuse and diffuse-in-aggregate, and paratracheal usually vasicentric,complete to aliform, rarely confluent and with terminal parenchyma bands associated with 2-4 vessels. Cristals are of two types and vcry frequent in rays and cells of axial parenchyma. Intercellular canals of traumatic origin are surrounded by parenchyma tissue.